(untitled) (Journal of Applied Oral Science, 2023)
Objective: To characterize activated charcoal and 2% hydrogen peroxide-based toothpastes and investigate their effects on roughness, color change, and gloss of bulk-fill composite resin. Methodology: Composite resin specimens (Aura Bulk Fill, SDI) were subjected to 5,000 brushing cycles with regular toothpaste (Colgate Total 12, [RT]), activated charcoal toothpaste (Bianco Dental Carbon, [AC]), or hydrogen peroxide-containing toothpaste (Colgate Luminous White Advanced, [HP]), with or without coffee exposure. The pH, particle characterization by scanning electron microscopy (SEM), and weight% of solid particles in the toothpaste were assessed. Roughness (Ra) was evaluated using a surface profile-measuring device, color change (∆Eab/∆E00) by reflectance spectrophotometer, and gloss unit (GU) by glossmeter. Kruskal–Wallis, Dunn, Friedman, and Nemenyi tests were used, and the correlation coefficient test was performed between Ra and GU (α=0.05). Results: RT presented a higher Ra after brushing and did not change after staining with coffee; moreover, the ∆Eab/∆E00 values were higher for RT than HP. Regarding gloss, AC and HP obtained higher values compared to RT. A significant negative correlation between gloss and Ra was found for RT exposed to coffee. All toothpastes had a neutral pH; however, RT had the largest percentage of solids by weight. SEM images showed particles of many sizes: irregular shape (RT), more regular particles (AC), and spherical clusters (HP). Although surface roughness, color change, and gloss may compromise the longevity of restorations, the whitening toothpastes tested did not promote more morphology changes than regular toothpastes.